Determining factors of SMEs marketing performance in Bandung City: Quantitative Approach - Veronika, Katharina; Munajat, Bambang Teguh; Purnama, Lany Rizki; Fauzan, M Faliq (Journal of Economics Education and Entrepreneurship, 2024)
This study aims to determine the interaction model between entrepreneurial orientation, product innovation, and competitive advantage on the marketing performance of fashion SMEs in Bandung City. The method used was simple random sampling with the main subjects being 100 owners or managers of fashion SMEs in Bandung City. Data were collected through questionnaires and analyzed using path analysis techniques with the help of SPSS software. The results showed that product innovation has a significant influence on the marketing performance of SMEs, while entrepreneurial orientation and competitive advantage did not show a significant influence. The findings emphasize the importance of product innovation in improving the marketing performance of SMEs in Bandung and indicate the need for further exploration of other factors to gain a more comprehensive understanding.